Orgilinae (Hymenoptera: Braconidae) en cultivo de café de Cravinhos, SP, Brasil - Tango, Maria F. A. [UNESP] (2014)
The aim of this study was to document the Orgilinae species found in Coffea arabica L. at Cravinhos, at Sao Paulo State, Brazil; to evaluate the population fluctuation of Orgilus niger, and to correlate it population with the sampling methods employed, with populations of Leucoptera coffeella, rainfall, and the average maximum and minimum temperatures. Orgilinids were collected weekly between May 2005 and April 2007 with Moericke and light traps. The following species were identified: O. niger (757 specimens; 88.0% of the total collected), Orgilus sp. 1 (71; 8.3%), and Stantonia longicornis (32; 3.7%). The highest frequency of Orgilinae was recorded between May 2005 and April 2006 (693; 80.6%), and O. niger between May and October 2005, with a peak population between August and September 2005. Moericke traps captured all the specimens of O. niger, S. longicornis and most Orgilus sp. 1; traps installed at the height of the lower third of the plants captured the highest average of O. niger, which differed significantly from those installed in the middle third. Between May 2005 and April 2006, the correlations between the population of O. niger and the number of larvae and mines of L. coffeella available for parasitism were positive and significant and negative and significant with the rainfall and minimum and maximum temperatures, indicating that periods of drought and lower temperature in the year favor the increase of the population of L. coffeella and its parasitoid O. niger.